HIV testing in a South African Emergency Department: A missed opportunity - Hansoti, Bhakti; Stead, David; Parrish, Andy; Reynolds, Steven J.; Redd, Andrew D.; Whalen, Madeleine M.; Mvandaba, Nomzamo; Quinn, Thomas C. (PLOS ONE, 2018)
Background South Africa has the largest HIV epidemic in the world, with 19% of the global number of people living with HIV, 15% of new infections and 11% of AIDS-related deaths. Even though HIV testing is mandated in all hospital-based facilities in South Africa (SA), it is rarely implemented in the Emergency Department (ED). The ED provides episodic care to large volumes of undifferentiated who present with unplanned injury or illness. Thus, the ED may provide an opportunity to capture patients with undiagnosed HIV infection missed by clinic-based screening programs. Methods and findings In this prospective exploratory study, we implemented the National South African HIV testing guidelines (counselor initiated non-targeted universal screening with rapid point of care testing) for 24-hours a day at Frere Hospital in the Eastern Cape from September 1st to November 30th, 2016. The purpose of our study was to quantify the burden of undiagnosed HIV infection in a South African ED setting. Furthermore, we sought to evaluate the effectiveness of the nationally recommended HIV testing strategy in the ED. All patients who presented for care in the ED during the study period, and who were clinically stable and fully conscious, were eligible to be approached by HIV counseling and testing (HCT) staff to receive a rapid point-of-care HIV test. A total of 2355 of the 9583 (24.6%) patients who presented to the ED for care during the study period were approached by the HCT staff, of whom 1714 (72.8%) accepted HIV testing. There was a high uptake of HIV testing (78.6%) among a predominantly male (58%) patient group who mostly presented with traumatic injuries (70.8%). Four hundred (21.6%) patients were HIV positive, including 115 (6.2%) with newly diagnosed HIV infection. The overall prevalence of HIV infection was twice as high in females (29.8%) compared to males (15.4%). Both sexes had a similar prevalence of newly diagnosed HIV infection (6.0% for all females and 6.4% for all males) in the ED. Conclusions Overall there was high HIV testing acceptance by ED patients. A non-targeted testing approached revealed a high HIV prevalence with a significant burden of undiagnosed HIV infection in the ED. Unfortunately, a counselor-driven HIV testing approach fell short of meeting the testing needs in this setting, with over 75% of ED patients not approached by HCT staff.